2012
DOI: 10.1038/eye.2012.262
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal methotrexate for the treatment of choroidal neovascularization in multifocal choroiditis

Abstract: Sir, Intravitreal methotrexate for the treatment of choroidal neovascularization in multifocal choroiditisWe describe a case of a patient who developed a multifocal choroiditis complicated with a choroidal neovascular (CNV) membrane, and propose an intravitreal methotrexate therapy as a treatment option that can improve vision and eliminate all inflammatory signs. Case reportA healthy 25-year-old woman presented with evidence of a multifocal choroiditis (MFC) complicated with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The specific role of inflammation in the pathogenesis of iCNV is also supported from other histological studies and the response observed following treatment of iCNV with immunosuppressive agents 5 6 9 10. Before anti-VEGFs were available, corticosteroids were the first-line treatment for iCNV and, in particular, corticosteroids in addition to PDT were more effective than PDT alone 25.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The specific role of inflammation in the pathogenesis of iCNV is also supported from other histological studies and the response observed following treatment of iCNV with immunosuppressive agents 5 6 9 10. Before anti-VEGFs were available, corticosteroids were the first-line treatment for iCNV and, in particular, corticosteroids in addition to PDT were more effective than PDT alone 25.…”
Section: Discussionmentioning
confidence: 75%
“…There are also some anecdotal reports of the use of other therapeutic agents such as intravitreal methotrexate9 and oral sirolimus 10…”
Section: Introductionmentioning
confidence: 99%
“…MTX therapy is indicated in almost all types of ocular inflammation, including anterior, intermediate, posterior, and panuveitis, retinal vasculitis, scleritis, childhood chronic uveitis, and mucus membrane pemphigoid [17][18][19]. Other specific indications include Behçet disease [20], birdshot chorioretinopathy [21], multifocal choroiditis with panuveitis [22,23], sarcoidosis [24], Vogt-Koyanagi-Harada disease [25], and sympathetic ophthalmia [26]. In addition, complications In pediatric patients, corticosteroid use is associated with a potential risk of irreversible growth suppression despite the presence of human growth hormones [31].…”
Section: Mtx For Ocular Inflammatory Diseasesmentioning
confidence: 99%
“…In addition, MTX can be administered intravitreally at a dose of 400 μg in 0.1 mL. Recently, several studies have shown that intravitreal injection of MTX is effective for the treatment of uveitis with no serious ocular side effects [20,23,[36][37][38]. Intravitreal administration can be advantageous because it can avoid the potential side effects of systemic corticosteroids and immunosuppressive agents, especially in patients with unilateral uveitis.…”
Section: Mtx For Ocular Inflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation